Endogenous growth, skill obsolescence and output hysteresis in a New Keynesian model with unemployment - Wolfgang Lechthaler; Mewael F. Tesfaselassie (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2021)
We embed human capital-based endogenous growth into a New-Keynesian model with search and matching frictions in the labor market and skill obsolescence from long-term unemployment. The model can account for key features of the Great Recession: a decline in productivity growth, the relative stability of inflation despite a pronounced fall in output (the "missing disinflation puzzle"), and a permanent gap between output and the pre-crisis trend output. In the model, lower aggregate demand raises unemployment and the training costs associated with skill obsolescence. Lower employment hinders learning-by-doing, which slows down human capital accumulation, feeding back into even fewer vacancies than justified by the demand shock alone. These feedback channels mitigate the disinflationary effect of the demand shock while amplifying its contractionary effect on output. The temporary growth slowdown translates into output hysteresis (permanently lower output and labor productivity).
urn:nbn:de:hebis:30:3-564462
Keywords: 330; endogenous growth; search and matching; unemployment; nominal rigidity; output hysteresis; monetary policy